Impacto da IA e IATF na cadeia produtiva da bovinocultura de corte - Braga, André Zaganin [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The beef cattle industry in Brazil has been growing exponentially in recent years, with this it is necessary that producers are constantly adapting and enjoying the technologies available in the market to keep up with this growth. From this, different biotechnologies are made available as alternatives so that the producer may improve productive efficiency of his herd. Currently, the main reproductive biotechnologies used in beef cattle are Artificial Insemination (IA) and Timed Artificial Insemination (TAI). The objective of this literature review is to present them, list the main impacts of these biotechnologies on production and present the reflection of these practices to the producer

O setor da pecuária de corte no Brasil vem crescendo exponencialmente nos últimos anos, com isso faz-se necessário que os produtores constantemente estejam se adaptando e usufruindo das tecnologias disponíveis no mercado para acompanhar esse crescimento. A partir disso, diferentes biotecnologias são disponibilizadas como alternativas para que o produtor possa melhorar a eficiência produtiva do seu rebanho. Atualmente as principais biotecnologias reprodutivas utilizadas na pecuária de corte consistem na Inseminação Artificial (IA) e na Inseminação Artificial em Tempo Fixo (IATF). O objetivo desta revisão de literatura é apresentá-las, elencar os principais impactos dessas biotecnologias na produção e apresentar o reflexo destas práticas ao produtor.
Impact of AI and TAI on the production chain of beef cattle
Keywords: Reproduction; Biotechnologies; Beef cattle; AI; TAI; Reprodução; Biotecnologia; Bovinocultura de corte; IATF; IA